Antenna selection algorithm based on cut-off rate for secure spatial modulation with finite alphabet input - Qingfeng DING; Tao XI; Qian YANG; Xu DING (Tongxin xuebao)
For the security transmission of artificial noise with finite alphabet inputs in secure spatial modulation system,an antenna selection algorithm based on cut-off rate (COR) was proposed.Considering that it was difficult to obtain the closed-form expression of the secrecy rate,the problem of maximizing the secrecy rate into that of maximizing the COR was converted by the algorithm.Meanwhile,in order to reduce the complexity,the COR algorithm was optimized by expanding the matrix norm in columns,which was corresponding to the problem of antenna combination.Finally,the artificial noise vector was mapped in the legitimate channel space to optimize secrecy rate,which only interferes with eavesdropper.The simulation results show that the proposed algorithm based on COR is superior to the leakage-based algorithm and the maximum secrecy rate algorithm,and has lower complexity.